Inactivation of Escherichia coli O157:H7 by essential oil from Cinnamomum zeylanicum - Senhaji,Ouafae (2007)
Escherichia coli O157:H7 is a pathogen strain, which causes hemorrhagic colitis, hemolytic uremic syndrome and thrombotic thrombocytopenic purpura in humans. The control of bacterial cells in foods is an important factor to reduce foodborne diseases due to E. coli O157:H7. Assays to inactivate E. coli O157:H7 were carried out by using the cinnamon oil obtained by steam distillation for 6 hours. When E. coli O157:H7 cells were incubated at 37°C for 2 hours in the presence of 0.025% of the essential oil from cinnamon, a dramatic decrease was observed in the viable counts (from 10(7) to 3.10(4) CFU/mL-1). In the presence of 0.05% of the oil, most of cells were killed after 30 min, suggesting that the antimicrobial activity of essential oil is bactericidal against E. coli. The minimal inhibitory concentration of the essential oil from cinnamon was around 625 ppm against E. coli O157:H7 and E. coli ATCC 25921, around 1250 ppm against E. coli ATCC25922 and around 2500 ppm against E. coli ATCC11105.